2000
DOI: 10.1159/000045780
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Final Adult Height after Renal Transplantation during Childhood: A Single-Center Study

Abstract: Aim: Assessment of final adult height and its predictive factors in children transplanted (RTx) and followed up in a single center. Methods: A cohort of 32 patients (17 boys, 15 girls) who received RTx before the age of 15 years and had reached a final adult height was selected. Twenty patients received a single RTx, 9 patients received two RTx, and 3 patients received three RTx. Seven children were transplanted preemptively, while the remaining 25 children received peritoneal dialysis for relatively short per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
(33 reference statements)
1
17
1
Order By: Relevance
“…Although improvements have been made in several aspects of treatment, target adult height has not been achieved in the majority of patients. The final height was below the 95% confidence limits for target height in 41% of children transplanted before the age of 15 years in a report by Rodriguez-Soriano, even though some of the patients had been treated with GH [14].…”
Section: Introductionmentioning
confidence: 69%
“…Although improvements have been made in several aspects of treatment, target adult height has not been achieved in the majority of patients. The final height was below the 95% confidence limits for target height in 41% of children transplanted before the age of 15 years in a report by Rodriguez-Soriano, even though some of the patients had been treated with GH [14].…”
Section: Introductionmentioning
confidence: 69%
“…In recent years, several single-center reports have specifically addressed final height after transplantation in childhood (9)(10)(11)(12)(13). The proportion of patients who achieved a final height within the normal range ranged from 47% to 75%, which appears considerably improved over early reports in which normal adult height was achieved in only 23%-38% (14,15).…”
Section: Introductionmentioning
confidence: 97%
“…8 However there are very few reports on adult height after rhGH therapy. The three patients reported by Offner et al 9 and the 3 patients reported by Rodriguez-Soriano et al 10 showed benefi cial effects of rhGH therapy. The mean adult height SDS values in these two studies 9,10 were −1.9 and −0.6.…”
Section: Discussionmentioning
confidence: 90%
“…Their height SDS was −2.7 at start of rhGH therapy and −1.8 at adult height. The reports by Offner et al, 9 Rodriguez-Soriano et al, 10 and Fine et al 13 had no information about steroid therapy. Administration of rhGH may affect the immune system and induce hyperfi ltration and may have deleterious effects on graft function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation